Reinforcement Steel Management Method and Its Implication on Construction Project Performance: Case Study in Pulau Pinang: : Case Study in Pulau Pinang - Mohd Nasir, Muhamad Zakwan; Syed Mohamad, Syed Burhanuddin Hilmi (Recent Trends in Civil Engineering and Built Environment, 2021)
Construction industry such as building infrastructure, house development requires a huge number of materials use. Based on the growth population there is a great demand on the building materials and supply management. Proper material management methods are needed to ensure the construction projects run smoothly. The objective of this study is to identify the effect of material management in construction industry and to determine the reinforcement steel materials management applied by companies in the construction industry in the area of Pulau Pinang. Therefore, this study is not only about the knowledge of material management methods applied at construction sites in Pulau Pinang but also the effect of material management methods on project performance. The purpose of this research is to assist contractors, project managers, quantity surveyors and those involved in the construction industry on how to enhance the effectiveness of existing materials management methods with some of the recommendations that have been stated put forward. A survey of questionnaire was carried out to obtain the data and information that needed for this study. A quantitative of 100 questionnaires will be distributed to a few selected construction companies around Pulau Pinang region. The method chose to analyse the data is by the software Statistical Package Social Science (SPSS) and using the Average Index analysis which are easier to calculate questionnaire data that are using Likert scale. Therefore, based on the results on the data analysis in Chapter 4, the first and second objective of this study can be achieved.